Responsive Sensory Evaluation to Develop Flexible Taste-Masked Paediatric Primaquine Tablets against Malaria for Low-Resource Settings - Sejal R. Ranmal; Marc Lavarde; Elodie Wallon; Samar Issa; Walter R. Taylor; Julie L. A. Nguyen Ngoc Pouplin; Catherine Tuleu; Anne-Marie (MDPI AG, 2023)
Primaquine is an important antimalarial drug for malaria transmission blocking and radical cure, but it is not currently available in child-friendly formulations in appropriate doses. Adult-strength tablets are often crushed and dissolved in water to obtain the required dose, which exposes the drug's bitter taste. As part of the developing paediatric primaquine (DPP) project, this study adopted a responsive sensory pharmaceutics approach by integrating real-time formulation development and pre-clinical taste assessment to develop palatable, flavour-infused primaquine tablets. A design of experiment (DoE) approach was used to screen different taste-masking agents and excipient blends with trained, expert sensory assessors, with quinine hydrochloride as a model bitter tastant. The taste-masking efficacy of selected prototype formulation blends was validated with naïve assessors using the highest 15 mg primaquine dose. The mean bitterness intensity rating, measured on a discrete 11-point scale, was halved from 7.04 for the unflavoured control to 2.74-3.70 for the formulation blends. Sucralose had the biggest impact on bitterness suppression and improving palatability. Two different flavouring systems have been developed, and their acceptability in paediatric patients will be assessed as part of upcoming validation field clinical trials in Africa.